1(2)gl gene regulates late expression of segment polarity genes in Drosophila. - Mukherjee, A.; Lakhotia, S.C.; Roy, J.K. (Mechanisms of Development, 1995)
To analyse the possible roles of Drosophila tumour suppressor genes, 1(2)gl and 1(2)gd, in differentiation programmes of imaginal cells, we investigated their interactions with two segment polarity genes, viz., cubitus interruptus Dominant (ci-D) and engrailed (en), by examining their patterns of expression in tumourous imaginal discs of 1(2)gl4 or 1(2)gd1 homozygous larvae. While the 1(2)gd1 mutation did not have much effect, the areas of expression of ci-D and en in the tumourous discs of 1(2)gl homozygous larvae were significantly increased and the anterior-posterior compartment boundary was no longer identifiable. To examine if the loss of en expression compartment boundary in 1(2)gl tumourous discs was due to overproliferation of the posterior compartment cells or due to a deregulated expression of en in the anterior compartment cells, 1(2)gl4 homozygous cell clones were generated in 1(2)gl4 enlacZ/++ background. A distinct X-gal staining in 1(2)gl homozygous clones in the anterior compartment in wing imaginal discs or in adult wings confirmed deregulated ectopic expression of en in 1(2)gl mutant anterior compartment cells. We suggest that 1(2)gl is involved in regulating post embryonic expression of segment polarity genes.